Analysis of Socio-Emotional Development in Four-Year-Old Broken Home Child in Nagari Simpang: A Case Study - Yola Andika Putri; Rismareni Pransiska (Universitas Pendidikan Indonesia Kampus Serang, 2021)
A broken home will impact the socio-emotional development of early childhood. Bad relationships in a family are the focus of this research problem. This study aims to describe the analysis of the socio-emotional development of a four-year-old broken home child in Nagari Simpang, a village in Simpang Alahan Mati Subdistrict, Pasaman Regency, West Sumetera Province. This descriptive qualitative research used a case study approach. The researchers collected data through observation, interviews, and documentation with one girl as subject of the study. The data analysis technique was done by data triangulation. The results showed that a broken home in a four-year-old child had a good and also bad impact on the child's socio-emotional development at the same moment. The impact was where the child could control and look at herself. However, in socializing, the girl imposed herself in an environment that often involved her. This finding provides an understanding to parents in developing socio-emotional abilities of early childhood in a broken home family.